Pengaruh Kemandirian Belajar dan Berpikir Kritis Terhadap Hasil Belajar Matematika Siswa - Lestari, Putri Bunga Citra; Ketut Sarjana; Dwi Novitasari; Nyoman Sridana (Mandalika Mathematics and Educations Journal, 2024)
This study aims to determine how learning independence and critical thinking influence the mathematics learning outcomes of grade 8th students at SMP Negeri 1 Mataram in academic year 2023/2024. This research is a quantitative with a research approach with an ex-post facto method. The population of this research was 402 students in grade 8th at SMP Negeri 1 Mataram. The sample size was 75 students who were determined using cluster random sampling techniques. The instruments in this research used an learning independence questionnaire, an critical thinking questionnaire, and a mathematics learning outcomes test in the form of essay questions. Data was analyzed using linear regression analysis it was found that there is a joint positive and significant relation between learning independence and critical thinking on the mathematics learning outcomes of grade 8th at at SMP Negeri 1 Mataram in academic year 2023/2024 with the regression equation. The correlation coefficient value is 0,875, that means to have a strong influence and contribution to learning outcomes is 76,5%.